ANALISIS KEAMANAN SISTEM INFORMASI MANAJEMEN DALAM PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP PT BANK CENTRAL ASIA Tbk. (BCA) - Edy Susanto; Hendrick Moses, Rendy Ramadan, Shabina Deanova (CV. ADIBA AISHA AMIRA, 2023)
The development of Internet banking in Indonesia will increase rapidly in line with developments in technology, market demand, geographical location and population. Structuring internet banking operations is needed to avoid problems in the future and facilitate supervision by Bank Indonesia.